Silencing Citizen Protest: Local Environmental Resistance in the Land of Fires - Scafuto, Francesca; Edelstein, Michael R. (PARTECIPAZIONE E CONFLITTO, 2020)
The main topic of this case study is local community response to environmental contamination resulting from corruption and waste mismanagement. The field research was carried out in part of a massive Italian district colloquially referred to as the "land of fires” where illegal wastes dumped by the mafia routinely burned. A document analysis, participant observation and semi-structured interviews were conducted. Abandoned by those tasked with protecting public and environmental health, one might expect widespread concern, activism and protest. The case study supports the theory in terms of citizen mobilization while clarifying conditions that discourage public protest and action. The waste companies and the governmental institutions intended to regulate them were perceived as jointly complicit. Those who did not protest appeared to be caught in a classic double bind in which any response they made was wrong. Fear that the contamination and fires were harming their health demanded action. Yet, citizens dreaded that such efforts would bring mob and institutions’ reprisal and did not have practical effective outcomes. This dilemma is fully explored, and the results are discussed within an eco-historical perspective. The case study is also updated to reflect more recent conditions that inspired widespread protest in the same affected region.